Моделювання сучасних атак на мережу блокчейн - Фесенко, Д. (ХНУРЕ, 2020)
The paper deals with the design and implementation attacks on different systems based on blockchain technology. Intruder model and threat model for blockchain networks created. Blockchain network attacks are analyzed and methods of defense against these attacks are proposed. Recommendations were made regarding the use of blockchain technologies, taking into account all the factors considered.
Keywords: блокчейн; імітаційне моделювання